Introducing Entrepreneurship Knowledge for Generation Alpha as the Key to Shaping Independent Generations in the Digital Era - Asmara, Maisa Azizah; Rifai, Muhammad Syakib Asqalami (Universitas Malahayati Lampung, 2024)
ABSTRACT Technological disruption is the greatest challenge that must be faced. Therefore, mental maturity is needed to understand and take advantage of its benefits while controlling oneself against its drawbacks. One way to achieve this is by fostering an entrepreneurial spirit from an early age. This effort aims to provide entrepreneurial knowledge to parents to create a generation that is independent, creative, and competitive in the future. By introducing the concept of entrepreneurship early on, it is hoped that Generation Alpha can develop the potential to become successful leaders and entrepreneurs in an increasingly complex era. This program uses counseling methods in the form of seminars and Q&A sessions. Community Service (PKM) was conducted at SB Kp. Pandan, Malaysia, with 36 participants. This PKM program successfully increased the participants' understanding of entrepreneurship by 64.38%, with 23 participants showing improved knowledge based on the questionnaires distributed before and after the counseling session. Overall, this program successfully enhanced the participants' entrepreneurial knowledge. Keywords: Knowledge, Entrepreneurship, Independence, Generation Alpha